Characteristics and kinetics of biohydrogen production with Ni2+ using hydrogen-producing bacteria. (5th January 2015) - Gou, Chenye; Guo, Jianbo; Lian, Jing; Guo, Yankai; Jiang, Zongshan; Yue, Lin; Yang, Jingliang
Abstract The characteristics and kinetics of biohydrogen production with Ni2+ using hydrogen-producing bacteria (HPB) obtained from cow dung were investigated in batch tests. The results indicated that cumulative biohydrogen production and hydrogen yield were enhanced with an increase of 0.3–6 mg/L in the Ni2+ concentration at 35 °C and an initial pH of 6.0. The maximum cumulative biohydrogen production was 442.52 mL, and the maximum hydrogen yield was 2.05 mol H2/mol sucrose at 0.6 mg/L Ni2+. Compared with the control, the cumulative biohydrogen production with 0.6 mg/L Ni2+ was doubled. The major soluble metabolites produced in this study were ethanol, acetate, and butyrate. In addition, the final pH was lower than the initial pH after the production of biohydrogen, and the substrate degradation efficiency was slightly enhanced with an increase in the Ni2+ concentration from 0.3 to 9 mg/L. Modified Gompertz and Han–Levenspiel models were used to describe the effects of Ni2+ on biohydrogen production, and the model predicted data fit the experimental results well. The mathematical constants n and m of these models were 103.59 and 2.69, respectively, suggesting that the reaction was uninhibited. The predicted critical Ni2+ concentration was 15.58 mg/L, which completely suppressed biohydrogen production. This study contributes to the improvement of organic waste utilisation by HPB.